2020
DOI: 10.1002/rcm.8607
|View full text |Cite
|
Sign up to set email alerts
|

Postsynthesis of zwitterionic hydrophilic composites for enhanced enrichment of N‐linked glycopeptides from human serum

Abstract: Rationale Glycosylation of proteins plays an important role in life activities, but the concentration of naturally occurring glycopeptides is usually relatively low, and glycosylation has microfacies heterogeneity, so direct mass spectrometry is not feasible. Therefore, selective enrichment of glycopeptides before mass spectrometry has turned into an urgent problem to be resolved. Methods Herein, the zwitterionic L‐cysteine functionalized hydrophilic graphene oxide composite (GO@PDA@MIL‐125‐NH2@Au@L‐Cys) was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In order to further investigate the selectivity of glycopeptide enrichment using different tips, sample mixtures of IgG digest and bovine serum albumin (BSA) digest with different weight mixing ratios were loaded onto the three kinds of tips for comparison. 18,37 Sample mixtures with the following IgG digest/BSA digest (IgG/BSA) weight mixing ratios were enriched: 1/10, 1/50, 1/100 and 1/150, corresponding to molar ratios of 1/23, 1/115, 1/230 and 1/345. After mixing the IgG digest with the BSA digest, a lot of non-glycopeptides could be detected in the elution fractions together with glycopeptides, no matter what kind of tip was used for enrichment ( Fig.…”
Section: Optimization Of Igg Glycopeptide Enrichment Conditions Usingmentioning
confidence: 99%
“…In order to further investigate the selectivity of glycopeptide enrichment using different tips, sample mixtures of IgG digest and bovine serum albumin (BSA) digest with different weight mixing ratios were loaded onto the three kinds of tips for comparison. 18,37 Sample mixtures with the following IgG digest/BSA digest (IgG/BSA) weight mixing ratios were enriched: 1/10, 1/50, 1/100 and 1/150, corresponding to molar ratios of 1/23, 1/115, 1/230 and 1/345. After mixing the IgG digest with the BSA digest, a lot of non-glycopeptides could be detected in the elution fractions together with glycopeptides, no matter what kind of tip was used for enrichment ( Fig.…”
Section: Optimization Of Igg Glycopeptide Enrichment Conditions Usingmentioning
confidence: 99%
“…A larger specific surface area means more anchor sites for subsequent materials, which can also be seen from the determination of the Zn element content of EDX. Similarly, Liu et al [36] . constructed GO@PDA@MIL‐125@Au@L−Cys using graphene as the base material showed a more outstanding performance than general magnetic microspheres during glycopeptide enrichment experiments, and both the limit of detection and selectivity were superior to an order of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…A larger specific surface area means more anchor sites for subsequent materials, which can also be seen from the determination of the Zn element content of EDX. Similarly, Liu et al [36] constructed GO@PDA@MIL-125@Au@LÀ Cys using graphene as the base material showed a more outstanding performance than general magnetic microspheres during glycopeptide enrichment experiments, and both the limit of detection and selectivity were superior to an order of magnitude. Through these comparisons, we can clearly see that the materials with a larger specific surface area as the substrate have preferable enrichment performance, which provides a clearer choice for us to pursue more extreme and superior phosphopeptides enrichment performance.…”
Section: Comparison Of the Performance Of Fe 3 O 4 @Pda@mtio 2 @Pei-g-zif-8 And Mcnt@pda@pei-zif-8 On Phosphopeptides Enrichmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycoprotein is composed of protein and sugar chains connected by covalent bonds and has high hydrophilicity, while nonglycosylated proteins are more hydrophobic, so the difference in hydrophilicity can be used to achieve glycoprotein enrichment. As a result, hydrophilic nanomaterials with a large number of hydrophilic groups have been explored and achieved good results in glycopeptides enrichment [25][26][27][28]. Recently, carbon-based materials are considered as convenient scaffolds for obtaining hybrid materials, not only because of their large specific surface area but also because they can be postmodified to have properties of magnetism, hydrophilicity, biocompatibility, and so on [29].…”
Section: Introductionmentioning
confidence: 99%